SRLG-disjointness and geodiverse routing – a practical network study and operational conclusions - Nedic, Boro (2018)
The problem of disaster resilience is of paramount importance in today's telecommunication networks. Here, this problem is tackled by considering 1+1 optical lightpath protection with maximally SRLG-disjoint paths and geodiversity in a transparent backbone network. Geodiversity was added to make the network more resilient to geographically correlated disasters. The aim is to estimate the increase of the path lengths (fibre lengths) and the increase in cost of the required transponders, with respect to simple link disjointness (no-SRLG nor geodiversity constraints) in a fully transparent optical network. The results obtained in a realistic test network show that SRLG-disjointness already ensures an acceptable geodiversity for the considered network.